EMPLOY STRATEGIC FLEXIBILITY IN ACHIEVING SUSTAINABLE COMPETITIVENESS OF IRAQI BANKS: A SURVEY OF BANKS IN SALAH AL-DIN GOVERNORATE - Firas Farhan Jedi; Kifah. A. Muhaimid; Ragad adnan Mahdi; Ahmed khudhair ahmed (Scholar Express Journals, 2022)
The research aims to identify the possibility of employing strategic flexibility in banks and adapting to environmental changes is one of the most important tools for gaining a sustainable competitive advantage. sustainable Iraqi banks. To achieve the objectives of the research, the opinions of a sample of employees were taken and analyzed using Partial Least Squares (PLS) application. And, we reached many results, the most important of which is the existence of a vital role for strategic flexibility in achieving sustainable competitive advantage. The researchers suggest to the management of Iraqi banks (Rasheed Bank & Rafidain Bank) the study sample with interest in applying the requirements of sustainable competitive advantage to interact with the banking environment effectively
Keywords: Strategic flexibility; Sustainable competitiveness; Iraqi banks